The needs of carers: applying a hierarchy of needs to a foster and kinship care context. (July 2019) - Fergeus, Josh; Humphreys, Cathy; Harvey, Carol; Herrman, Helen
As foster and kinship carers are central to the lives of looked after children, it is important to recognise their unmet needs and the impact of these on the caring task. This article explores these issues by applying a hierarchy of needs to the foster and kinship care context, drawing on the perspectives of those involved. A group of Australian foster carers ( n  = 52) and kinship carers ( n  = 16) were interviewed using the CUES-C, a 13-item questionnaire that collects both qualitative and quantitative responses with regard to carers' perceived needs and satisfaction. Thematic analysis was undertaken and participant responses were coded and organised according to the updated hierarchy of human motives proposed by Kenrick and colleagues (2010), based onMaslow's (1943) widely used hierarchy of needs. The findings support Lyubomirsky and Boehm's (2010) conclusion that parenting may interfere with the capacity to meet our other human needs and so has significant implications for the form of intensive parenting practised by foster and kinship carers. It was found that without the provision of timely and holistic supports and intervention, the two-way relationship between the needs of looked after children and their carers may create a feedback loop where stress and trauma can be endlessly amplified, to the detriment of both parties. The evidence highlights the importance of addressing both the needs of carers and those of the young people they look after, and suggests some basic improvements that could ease the burden of care and simultaneously increase satisfaction in the caring role.